2018
DOI: 10.1111/nyas.13616
|View full text |Cite
|
Sign up to set email alerts
|

What is attentional refreshing in working memory?

Abstract: Working memory is one of the most important topics of research in cognitive psychology. The cognitive revolution that introduced the computer metaphor to describe human cognitive functioning called for this system in charge of the temporary storage of incoming or retrieved information to permit its processing. In the past decades, one particular mechanism of maintenance, attentional refreshing, has attracted an increasing amount of interest in the field of working memory. However, this mechanism remains rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 69 publications
(133 reference statements)
5
106
2
1
Order By: Relevance
“…They observed that these dual-task conditions reduced spatial memory span compared to the single-task blank condition, and this reduction was more accentuated when the distractor task was visuospatial. These results suggest that that reactivates representations thereby preventing them from getting lost Camos et al, 2018) or that refreshing boosts the accessibility of WM representations above baseline (Souza & Oberauer, 2017;Souza, Rerko, & Oberauer, 2015). Results from the blank condition in all experiments, show that spatial representations are getting lost throughout the retention interval in a way that refreshing cannot fully counteract.…”
Section: Discussionmentioning
confidence: 77%
“…They observed that these dual-task conditions reduced spatial memory span compared to the single-task blank condition, and this reduction was more accentuated when the distractor task was visuospatial. These results suggest that that reactivates representations thereby preventing them from getting lost Camos et al, 2018) or that refreshing boosts the accessibility of WM representations above baseline (Souza & Oberauer, 2017;Souza, Rerko, & Oberauer, 2015). Results from the blank condition in all experiments, show that spatial representations are getting lost throughout the retention interval in a way that refreshing cannot fully counteract.…”
Section: Discussionmentioning
confidence: 77%
“…Initially, it has been proposed that by semantically enriching representations in WM through elaboration, these transform into associative structures in LTM, and thus benefit WM in two ways: 1) Information transferred into LTM frees capacity in WM and 2) elaborately enriched representations provide stronger retrieval cues than those of representations that were simply repeated through articulatory rehearsal. Further, a maintenance process called attentional refreshing has been proposed, which has been shown to be distinct from articulatory rehearsal and elaboration (Bartsch, Singmann, & Oberauer, 2018;Camos et al, 2018;Johnson, Reeder, Raye, & Mitchell, 2002;Raye, Johnson, Mitchell, Greene, & Johnson, 2005). Refreshing is understood as a domain-general process through which representations in WM are reactivated during maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have also posited and studied a higher-speed version of refreshing that operates over all WM representations serially, fleetingly, and relatively automatically in service of WM maintenance(Barrouillet, Bernardin & Camos, 2004;Camos et al, 2018). This "swift" refreshing has been likened to plate spinning, in that each representation is visited in turn, receiving a slight boost in activity that maintains its neural momentum until it is next visited again.…”
mentioning
confidence: 99%